Burden and treatment seeking behaviour in chronic kidney disease patients: a cross-sectional descriptive study - Dhania, Bindiya; Kumar, Ashok; Kalal, Nipin; Bajpai, Nitin Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: CKD is a debilitating condition accountable for high morbidity and an overall burden on society and Government. The study objectives were to assess the burden and treatment seeking behaviour of CKD patients and to determine the association of demographic variables with burden and treatment seeking behaviour in CKD patients. Methods: A Descriptive survey research design was conducted on CKD Patients. 220 CKD patients were selected and a self-structured burden rating scale was used to assess the level of burden and treatment seeking behaviour checklist was used to find out the level of treatment seeking behaviour in CKD patients. Data were collected through face to face or telephonic interview by using non-probability convenient sampling technique. Results: Among 220 patients, majority of CKD patients had hypertension as comorbidity. More than half of CKD patients had moderate level of burden. CKD patients had highest burden in emotional domain. Majority of CKD patients ‘feel muscle cramps’ in level of burden. More than half of CKD patients had fair level of treatment seeking behaviour. CKD patients had highest treatment seeking behaviour in personal domain. There was significant association of burden and treatment seeking behaviour with demographic variables. Conclusions: Majority of CKD Patients had moderate level of Burden and fair level of treatment seeking behaviour. It was found that there was a significant association of burden and treatment seeking behaviour with demographic variables. The health care seeking behaviour of CKD patients drive them to come for treatment.